Drought is a major yield loss factor for rainfed East African highland banana - Asten, Piet J.A. van; Fermont AM; Taulya, Godfrey (Elsevier, 2011)
Although drought stress has been identified among the production constraints of East African highland bananas (Musa spp., AAA-EA genome), no quantitative data were available to support this assumption. This study uses data from three on-station fertilizer trials (5 6 cycles) in Central and Southwest Uganda to quantify the effect of drought stress on banana production and explore possible interactions with nutrient availability. Production data were collected at individual plant basis from 1996 to 2002 in one trial and from 2004 to 2009 in two trials. Cumulative rainfall in the 12 months before harvest (CRF12) was computed per plant from daily rainfall measurements. Average bunch weight ranged from 8.0 to 21.9 kg between trials and cycles and was 8 28% less in dry (CRF12 ? 905 mm) than in normal (905 < CRF12 ? 1365 mm) rainfall periods. Linear relations were observed between CRF12 and maximum bunch weight over the whole range of observed CRF12 (500 1750 mm), whereby every 100 mm decline in rainfall caused maximum bunch weight losses of 1.5 3.1 kg or 8 10%. Optimum annual rainfall for East African highland bananas may thus be well above 1200 1300 mm yr?1 as suggested earlier. Relative drought-induced yield losses were independent of soil fertility. Absolute losses on fertile/fertilized soils were similar to those recorded in well fertilized irrigation studies in Latin America. Our study suggests that drought-induced yield losses in areas of the East African highlands with annual rainfall < 1100 mm are perhaps as high as 20 65% compared to the wetter areas in this region. To improve productivity of smallholder banana farmers in Africa, more attention should be given to research geared towards improved water/drought stress management.